TINJAUAN YURIDIS TENTANG PENANGANAN PEMBUNUHAN BERENCANA YANG DISERTAI PENCURIAN TERHADAP KORBAN ( STUDI KASUS PUTUSAN PENGADILAN NEGERI SORONG NOMOR : 160/Pid.B/2023/PN Sor ) - Mambraku, Merlin; Syauta, Novalin M.; Baho, Dayen (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study explores the legal review of the handling of premeditated murder cases accompanied by theft, as well as the considerations made by judges when imposing sentences on perpetrators. This criminal act is a serious offense that not only harms the victim but also has widespread implications for society, undermining public safety and trust in the legal system. Through an analysis of Article 340 of the Criminal Code concerning premeditated murder and Article 365, paragraph 3 regarding theft with violence, it is found that both articles provide a crucial legal foundation for addressing this issue. A firm and consistent law enforcement approach is necessary to create a deterrent effect and prevent the recurrence of similar crimes in the future. In this study, the author also evaluates that the considerations made by the panel of judges in ruling No. 160/PID.B/2023/PN.SON comply with applicable legal standards. This finding is based on testimonies from witnesses and the defendant indicating that the defendant can be held accountable for their actions, although they were intoxicated at the time. The recommendations provided in this study emphasize that the Public Prosecutor should be more meticulous and careful in drafting the indictment, paying attention to the intent or mental state of the defendant in committing the crime. This intent should not only be based on the defendant's admission but also assessed based on the manner in which the perpetrator committed the criminal act.Keywords : Premeditated Murder,Theft,Law Enforcement,Evidence,Sentencing